Pembelajaran Bermakna Berbasis Post It - Restu Andrian (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2017)
Learning is the core activity of a process that must be traversed by learners in formal education. Exciting learning becomes the dream of every educational component. Learning process is not only interpreted as a process of interaction between teachers and students alone, but can be viewed more widely and comprehensively where there are also media and learning models. The learning process is expected to increase students' understanding. The students' understanding is not only limited to the memorization of learning theories without understanding the core and the concept of own learning and the development of mindset. Meaningful learning becomes one of the solutions to create an ideal learning process. This study aims to develop a meaningful learning process based on post it. Post it as a medium and then used as an intermediary toward meaningful learning process. Meaningful learning leads to the results of thinkers of learners, the results of thinkers learners can be achieved through the interaction of science and teacher insight, the phenomenon of society, scholarly cognitive subjects and student environmental phenomenon. So that the learning process will run well if managerial by teachers who are innovative and creative.